2015
DOI: 10.1016/j.ejvs.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Treatment of Haemorrhaging Coeliac or Mesenteric Artery Aneurysms and Pseudoaneurysms in the Era of Endovascular Management

Abstract: Patients needing emergency treatment of a VAA could be well served by non-surgical management. When the initial attempt at control of bleeding is unsuccessful it is important to consider non-conventional means of accessing these arteries. The need for surgery, in selected centres, may exist for a small group of patients after initial failed radiological treatment only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
4
25
0
3
Order By: Relevance
“…In contrast, the mortality rate is 0 % in our own study population and comparable results were seen in other studies (3 -7 %) [8,13,20]. However, some studies have shown that emergency interventional therapy has a significantly higher mortality rate of up to 17 % compared to elective therapy [21]. This result was not confirmed in our own study population.…”
Section: Discussionsupporting
confidence: 66%
“…In contrast, the mortality rate is 0 % in our own study population and comparable results were seen in other studies (3 -7 %) [8,13,20]. However, some studies have shown that emergency interventional therapy has a significantly higher mortality rate of up to 17 % compared to elective therapy [21]. This result was not confirmed in our own study population.…”
Section: Discussionsupporting
confidence: 66%
“…In a series of 48 patients with bleeding aneurysms, 45 (94%) were pseudoaneurysms. 289 Bleeding was a more frequent indication for intervention in pseudoaneurysms in another report (63% vs. 18% for true aneurysms). 17 Others have also published similar observations.…”
Section: Treatmentmentioning
confidence: 89%
“…287 False aneurysms of the mesenteric arteries may result from acute or chronic local inflammatory or infectious disease, commonly pancreatitis, or may result from trauma (including iatrogenic injuries during hepatobiliary procedures). 279,288,289 In some cases, no causal relationship can be established.…”
Section: Diagnosismentioning
confidence: 99%
“…Demgegenüber stehen eine Mortalität von 0 % im eigenen Untersuchungskollektiv sowie vergleichbare Ergebnisse anderer Studien (3 -7 %) [8,13,20]. Die Ergebnisse anderer Studien zeigen jedoch auch, dass die notfallmäßige interventionelle Behandlung gegenüber der elektiven Therapie eine deutlich höhere Mortalität von bis zu 17 % aufweist [21]. Dieses Ergebnis wurde im eigenen Untersuchungskollektiv so nicht bestätigt: Die notfallmäßige Behandlung führte nicht zu einer signifikant höheren Mortalität.…”
Section: Erfolgsrate Merkeunclassified